2004
DOI: 10.1128/aem.70.2.758-764.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tetracycline on Transfer and Establishment of the Tetracycline-Inducible Conjugative Transposon Tn 916 in the Guts of Gnotobiotic Rats

Abstract: We have investigated the transfer of Tn916 among strains of Enterococcus faecalis OG1 colonizing in the intestines of gnotobiotic rats. This animal model allows a low limit of detection and efficient colonization of the chosen bacteria. The animals continuously received tetracycline in drinking water. A tetracycline-sensitive recipient strain was allowed to colonize the animals before the resistant donor was introduced. The numbers of donors, recipients, and transconjugants in fecal samples and intestinal segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 41 publications
3
35
1
Order By: Relevance
“…Tn916 confers resistance to tetracycline in the host cell. The results obtained by using these strains were reported previously (2).…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Tn916 confers resistance to tetracycline in the host cell. The results obtained by using these strains were reported previously (2).…”
Section: Methodssupporting
confidence: 71%
“…1) indicates a homogeneous expression of gfp in all E. coli MC4100/pTGFP2 cells. Simultaneous colonization studies of two isogenic E. faecalis OG1 strains, one of which was tetracycline resistant, were performed with the animals used in the present study and were reported previously (2). The results of that study showed that the two isogenic E. faecalis strains were able to coexist in the intestines of rats receiving up to 50 g of tetracycline/ml of drinking water, which is well above the inhibitory concentration for the sensitive strain and suggests the existence of tetracycline-depleted microhabitats in the intestinal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in our studies, in vivo conjugal transfer of the tet(M) gene from L. lactis donor strains was also observed. In other studies, no secondary conjugal transfer from transconjugants was detected (5,29). The subtherapeutic administration of tetracycline to rats was intended to promote the spread of antibiotic resistance genes, as this effect has been reported earlier (5,34,47).…”
Section: Discussionmentioning
confidence: 99%
“…Chee-Sanford et al 8) also suggested that the fact that several species of Enterococcus possessed the same allele of tet(M) indicated the likelihood of the transfer of tet(M) among species. Although we did not measure the concentration of OTC in this study, Baul et al 4) demonstrated that low concentrations of tetracycline promote the transfer of tet(M) mediated by Tn916. The administered drug may not only apply selective pressure to retain the resistance gene but also may force the transfer of the resistance gene in the aquaculture environment.…”
Section: Discussionmentioning
confidence: 99%